(untitled) (Communications in Mathematical Research, 2021)
In this note, we establish several results concerning the gliding hump properties of matrix domains. In order to discuss F-WGHP, we introduce the U AK-property and find that this sort of property has close relationship with F-WGHP. In the course of discussing F-WGHP and WGHP of (c_0)_C_n , we discuss the F-WGHP and WGHP of the almost-null sequence space f_0.